Psychological distress among Bangladeshi physicians: roles of perceived stigma, fear of infection and resilience in the context of Covid-19 pandemic. Issue 1 (2nd January 2022) - Khan, Sanjida; Akter, Shamima; Khan, Tarina; Shariar, Golam; Awal Miah, Mohammad Abdul
ABSTRACT: While physicians' combat against the Covid-19 pandemic is itself stressful, their stigma experiences and fear of infection due to professional commitments may risk their psychological state. The study investigated the association among perceived stigma, fear of infection, resilience, and psychological distress among physicians during the Covid-19 pandemic in a developing country, Bangladesh. A total of 209 physicians voluntarily participated in a web-based cross-sectional survey. The Bangla translated version of the fear assessment questionnaire, perceived stigma scale, brief resilience scale, and the Kessler psychological distress scale was employed to assess fear of infection, perceived stigma concerning the Covid-19 pandemic, resilience, and psychological distress, respectively. Results showed that female physicians were more fearful, less resilient, and highly distressed compared to males. Young physicians and those who served Covid-19 patients perceived higher stigma than their counterparts. An intense fear, high perceived stigma, and low resilience were significantly associated with increased psychological distress, while perceived stigma was the most potent factor. Bangladeshi physicians might be more distressed due to the perceived stigma over the fear of Covid-19 infection. The findings highlighted the importance of psychological care for the physicians and designing effective awareness programs for the community people to intervene in the stigmatization circle.